Ψαράς στο ποδήλατό του κουβαλώντας παράνομη παγίδα για τη σύλληψη ψαριών στη λίμνη Κερκίνη - Β. Ψαλλιδάς (1991)
Ψαράς στο ποδήλατό του κουβαλώντας παράνομη παγίδα για τη σύλληψη ψαριών στη λίμνη Κερκίνη